Raman scattering obtained from laser excitation of MAPbI3 single crystal. (June 2020) - Ben-Uliel, Tal; Aviv, Hagit; Zhou, Junjie; Li, Minghao; Avadyayev, Shalom; Kapon, Omree; Damle, Vinayaka; Yi, Chenyi; Tischler, Yaakov
Graphical abstract: Highlights: Phase transition of MAPbI3 from tetragonal to cubic was induced by laser excitation of over 15 mW. Decomposition of MAPbI3 involve the generation of PbI2(s) which can further degrade to form I2(g) . Under laser excitation, the core of the focus indicated full decomposition. Resonant Raman scattering of the spontaneous Raman band of iodine at 213 cm −1 was detected. Raman stimulation of I2(g) was enabled due to the unique properties of MAPbI3 single crystal. Abstract: Finding renewable energy sources is of paramount importance to meet the increasing global energy demand whilst minimizing the impact on the environment. The research community has focused on solar energy as it is endlessly available, and have ranked the methylammonium lead iodide (MAPbI3 ) as one of the most promising candidate amongst perovskite solar cells. Despite its high efficiency, the MAPbI3 is sensitive to humidity, light, and temperature, its instability affects primarily on the crystalline structure and eventually leads to degradation. Three crystalline structures are known for this material, orthorhombic, tetragonal, and cubic which exist in different temperatures. Here we report on several processes detected from laser excitation of MAPbI3 single crystal at ambient conditions. A phase transition from tetragonal to cubic phase was induced by excitation of over 15 mW laser power. The phases were characterized by LF-Raman and photoluminescence, taken simultaneously with the increase of exciting laser power and the spectral changes were assigned to the structural differences. In addition, Raman stimulation of iodine vapors signal was observed, those vapors were generated from the core of the focus wherein the highest temperature led to degradation. The stimulated Raman phenomenon was enabled due to the unique properties of the MAPbI3 single crystal and revealed viability to use this material for additional applications in other research fields.